Parâmetros de predição de risco cardiovascular em pacientes infectados pelo HIV - Milena Maria Moreira Guimaraes (2009)
Introduction: The epidemic resulting from infection by the human immunodeficiency virus (HIV) continues to spread in an alarming manner and WHO estimates that 33 million individuals are living with HIV worldwide in 2007. Following the introduction of highly active antiretroviral therapy (HAART), HIV infection assumed the characteristics of a chronic disease in which good immunological and virological control is reached in the great majority of cases. Nevertheless, adverse reactions to drugs represent challenges that have to be confronted by the entire team providing care to the HIV-infected patient. Metabolic abnormalities (dyslipidemia and alterations in glucose homeostasis) and changes in body fat, which were first described in HIV patients following the introduction of combined antiretroviral therapy, are recognized cardiovascular risk factors in the general population. The general objective of this study was to assess predictive cardiovascular risk factors in HIV-infected patients undergoing antiretroviral therapy and in those who were not undergoing therapy. The specific objectives of the study were to evaluate the association between antiretroviral use and highly sensitive C-reactive protein (hs-CRP) levels; to correlate hs-CRP levels with traditional cardiovascular risk factors and parameters associated with the HIV-infection itself, and to compare the Framingham, SCORE (Systematic Coronary Risk Evaluation) and PROCAM (Prospective Cardiovascular Münster) evaluation equations of cardiovascular risk in HIV-infected patients with no clinically apparent cardiovascular disease.Methodology: This thesis comprises three papers. In the first paper, studies published in the medical literature dealing with cardiovascular complications in HIV-infected patients, principally ischemic diseases, prior to and following use of HAART were reviewed. Greater emphasis was given to longitudinal studies evaluating the incidence of cardiovascular events in the HIV-infected population. The second paper evaluated hs-CRP levels in patients treated or not treated with HAART and their correlation with traditional cardiovascular risk factors such as glucose and plasma lipid levels and with factors associated with the HIV-infection itself such as viral load and CD4+ lymphocyte count. A total of 171 patients were evaluated, 129 users of antiretroviral drugs and 42 non-users. Their work up included anthropometric evaluation, blood pressure measurement, laboratory tests, ultrasonography for the measurement of intraabdominal fat and impedancometry. The third paper compared equations for calculating cardiovascular risk (Framingham, SCORE and PROCAM) in HIV-infected patients with no known signs of cardiac disease. A total of 220 patients were included, 164 HAART users and 56 non-users. Results: First paper: The majority studies involving large populations of HIV-infected individuals evaluated for long periods of time have shown higher incidence of cardiovascular events when compared to the general population. Nevertheless, these data remain controversial and prospective studies designed to evaluate this question are needed. Second paper: Plasma hs-CRP levels were higher in patients undergoing HAART therapy (p<0.001). Hs-CRP levels above 3 mg/dl, considered to represent a high risk for cardiovascular complications, were found in 56% of patients on HAART. A positive correlation was found between hs-CRP levels and waist circumference (p=0.004), waist to hip ratio (p<0.001), systolic (p=0.05) and diastolic blood pressure (p=0.03), intraabdominal fat measured by ultrasonography (p=0.02), plasma triglyceride levels (p=0.001), total cholesterol (p=0.01), fasting glucose (p<0.01), and glucose (p<0.001) and insulin levels (p=0.02) 2 hours after glucose overload. No correlation was found with CD4 lymphocytes and viral load. Factors independently associated with hs-CRP levels in the model 1 multivariate analysis were non-nucleoside reverse transcriptase inhibitor (NNRTI) therapy (p=0.003), waist to hip ratio (p=0.006), fasting glucose (p=0.049) and glucose 2 hours after overload (p=0.003). In model 2 multivariate analysis, independent factors were NNRTI therapy (p<0.001), therapy with protease inhibitors (p=0.016) and metabolic syndrome (p=0.022). Third paper: A total of 220 HIV-infected patients were evaluated, 164 on HAART and 56 treatment naïve. The estimated prevalence of patients with an elevated 10-year risk of cardiovascular events was 3.7%, 2.0% and 1.9% according to the Framingham, PROCAM and SCORE equations respectively. The degree of agreement between the Framingham and PROCAM equations was moderate (Kappa = 0.412; p < 0.001), while agreement was low between Framingham and SCORE (Kappa = 0.222; p<0.001) and moderate between PROCAM and SCORE (Kappa = 0.438; p < 0.001). Conclusions: Concern regarding the increased risk of cardiovascular events among HIV-infected patients deserves further attention, since various studies have indirectly suggested an increased risk. Risk factors identified in these studies include an increase in inflammatory response markers, such as hs-CRP and interleukins, and an increase in prothrombotic markers such as fibrinogen and von Willebrand factor, while other studies have shown an increase in the thickness of the intima and media layers of the arteries and an increase in the number of atherosclerotic plaques in these patients. Evaluation of hs-CRP levels in this population showed that elevated levels are associated with classic cardiovascular risk factors and with the use of antiretroviral drugs. Individual evaluation of patients to predict cardiovascular risk is very important, since this would help improve the management of each particular patient. Three cardiovascular risk equations (Framingham, PROCAM and SCORE) were compared; however, correlation among these methods was merely low to moderate. Only longitudinal studies designed to evaluate the incidence of events in this particular population will be capable of defining the optimal individual predictive method in these patients. The majority of the prospective studies evaluating the incidence of cardiovascular events indicate an increased incidence of these events in HIV-infected patients. Nevertheless, new studies with longer observation period are required in order to define the actual incidence of cardiovascular events in this population.